Activating Transcription Factor 3, a Useful Marker for Regenerative Response after Nerve Root Injury - Lindå, Hans; Sköld, Mattias K.; Ochsmann, Thomas (Frontiers in Neurology, 2011)
Activating transcription factor 3 (ATF3) is induced in various tissues in response to stress. In this experiment, ATF3 expression was studied in adult rats subjected either to a dorsal or ventral root avulsion (L4-6), or sciatic nerve transection. Postoperative survival times varied between 1,5 hours to 3 weeks. In additional experiments an avulsed ventral root was directly replanted to the spinal cord. Dorsal root ganglias (DRGs) from humans exposed to traumatic dorsal root avulsions were also examined. After sciatic nerve transection ATF3 immunoreactivity (ATF3 IR) was detected in a few DRG neurons already 6 hours (h) after the lesion. After 24h the number had clearly increased and still at 3 weeks DRG neurons remained labeled. In the ventral horn, ATF3 IR in motoneurons was first detected 24h after the sciatic nerve transection, and still 3 weeks postoperatively lesioned motoneurons showed ATF3 labeling. After a ventral root avulsion many spinal motoneurons showed ATF3 IR already after 3h, and after 6h all motoneurons were labeled. At 3 weeks a majority of the lesioned motoneurons had died, but all the remaining ones were labeled. When an avulsed ventral root was directly replanted, motoneurons survived and were still labeled at 5 weeks. In DRG, a few neurons were labeled already at 1,5h after a dorsal root avulsion. At 24h the number had increased but still only a minority of the neurons were labeled. At 3 days the number of labeled neurons was reduced, and a further reduction was at hand at 7 days and 3 weeks. In parallel, in humans, 3 days after a traumatic dorsal root avulsion, only a few DRG neurons showed ATF3 IR. At 6 weeks no labeled neurons could be detected. These facts imply that ATF3 response to axotomy involves a distance dependent mechanism. ATF3 also appears to be a useful and reliable neuronal marker of nerve lesions even in humans. In addition, ATF3 up-regulation in both motor and sensory neurons seems to be linked to regenerative competence.